Cinnamon Bittern, Ixobrychus cinnamomeus (Gmelin) from Annapurna Conservation Area, Nepal - Baral, Rishi; Dahal, Tulasi P; Thapa, Suresh; Gurung, Dhan K; Acharya, Raju (ZOO-Journal, 2019)
No abstract available.